2021
DOI: 10.3390/ijms22189700
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Gut Microbiome, Lung Conditions, and Coronary Heart Disease and How Probiotics Affect These

Abstract: The importance of a healthy microbiome cannot be overemphasized. Disturbances in its composition can lead to a variety of symptoms that can extend to other organs. Likewise, acute or chronic conditions in other organs can affect the composition and physiology of the gut microbiome. Here, we discuss interorgan communication along the gut–lung axis, as well as interactions between lung and coronary heart diseases and between cardiovascular disease and the gut microbiome. This triangle of organs, which also affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 125 publications
0
3
0
1
Order By: Relevance
“…As a stress event, the stroke will activate the sympathetic nervous system, hypothalamic–pituitary–adrenal axis, and enteric nervous system, increasing the permeability of the intestinal mucosal barrier and the translocation of gut microbiota [ 20 , 31 ]. With the close association between the gut and the lung, gut dysbiosis could influence pulmonary health [ 32 ]. Chen et al reported that commensal gut microbiota played a vital role in immune defense against Escherichia Coli pneumonia by inducing the expression of Toll-like receptor 4 (TLR) and activation of nuclear factor κB [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a stress event, the stroke will activate the sympathetic nervous system, hypothalamic–pituitary–adrenal axis, and enteric nervous system, increasing the permeability of the intestinal mucosal barrier and the translocation of gut microbiota [ 20 , 31 ]. With the close association between the gut and the lung, gut dysbiosis could influence pulmonary health [ 32 ]. Chen et al reported that commensal gut microbiota played a vital role in immune defense against Escherichia Coli pneumonia by inducing the expression of Toll-like receptor 4 (TLR) and activation of nuclear factor κB [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, greater serum concentrations of FGF23 were found to be linearly associated with the total atherosclerosis burden (Mirza et al, 2009), heart failure, and also, an all-cause mortality (Udell et al, 2014) (Parker et al, 2010). B. Trimethylamine N-oxide (TMAO)-TMAO produced by the gut microbiota in body has been directly co-related with atherosclerotic heart disease (Wassenaar et al, 2021) (Schiattarella et al, 2017) (Stubbs et al, 2016). It is known to increase vascular inflammation by activating NF-κB (Seldin (Liu et al, 2019).…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…Although there are several studies describing the ability of probiotics, prebiotics, and postbiotics to reduce clinical severity in other respiratory diseases, for COVID-19, there are not yet any conclusive results [ 250 ]. A study by Ceccarelli et al, consisting of a cohort of patients who tested positive for SARS-CoV-2, characterized their GM.…”
Section: Microbiota–gut–lung Axis (Mgl)mentioning
confidence: 99%